2009
DOI: 10.1002/app.29555
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of styrene–butylacrylate emulsion copolymers modified by silane compounds

Abstract: Styrene (St)/butyl acrylate (BA) copolymers were prepared by adding triethoxyvinylsilane (TEVS), trimethoxyvinylsilane (TMVS), and triphenylvinylsilane (TPVS), each one through emulsion copolymerization. The polymerization was performed with methacrylic acid and auxiliary agents at 80 C in the presence of potassium peroxodisulfate as the initiator. Nonylphenol ethylene oxide-40 units (NP-40) and sodium lauryl sulfoacetate were used as nonionic and anionic emulsifiers, respectively. The resulting copolymers wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…However, the extent of its in corporation in the polymer chain has not measured. The experimental results show that the reaction rate decreases by increasing TMSETMIM and the same results were obtained for the other silane compounds [38][39][40][41][42]. It is known that the rates of propagation and consequently copolymerization in a radical copoly merization reaction are inversely related to the termi nation rate constant.…”
Section: Effect Of Tmsetmim Concentration On Reaction Ratesupporting
confidence: 69%
“…However, the extent of its in corporation in the polymer chain has not measured. The experimental results show that the reaction rate decreases by increasing TMSETMIM and the same results were obtained for the other silane compounds [38][39][40][41][42]. It is known that the rates of propagation and consequently copolymerization in a radical copoly merization reaction are inversely related to the termi nation rate constant.…”
Section: Effect Of Tmsetmim Concentration On Reaction Ratesupporting
confidence: 69%
“…The results represented in Figure C showed that the elastic modulus increased linearly as the percentage of sisal fibers increased within the composites. As the interfacial adhesion between fiber and polymer is improved, the transfer of stiffness from more stiff fiber to less stiff polymeric matrix increases as indicated from the higher elastic modulus value recorded for the 20HCFb composite …”
Section: Resultsmentioning
confidence: 99%
“…[32,33] The Si O Si asymmetric stretching vibration in the range of 1000 to 1100 cm −1 is characteristic of VTMS. [34] Figure 2B shows the FTIR spectra analysis of UF and CF. The peak at 3350.1 cm −1 corresponds to the stretching vibration of cellulosic OH groups.…”
Section: Biodegradationmentioning
confidence: 99%
See 1 more Smart Citation
“…Addition of silane compounds in acrylic emulsion provides beneficial effects by improving various mechanical properties, such as water, weather ability, good acid, and alkali resistance. [13][14][15][16][17][18] In addition to this, the incorporation of silicone plays the roles of coupling agent and softener 19 and it is enriched on surface of the film. 20 On the other hand You et al 21 demonstrated that silanes can be bonded with hydroxyl groups on the surface of substrate to increase the adhesion and also FTIR analysis indicated that organic functional silanes can be polymerized with other monomers.…”
Section: Resultsmentioning
confidence: 99%